THE ROLE OF COMPETENCE, ORGANIZATIONAL CULTURE, AND TAUHID IN WORK MOTIVATION WITHIN CONSULTING MSMES IN PEKANBARU CITY - Amiruddin Siregar; Sri Indrastuti; Hamdi Agustin; Sufian Hamim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study explores the role of competence, organizational culture, and tauhid in shaping work motivation among employees of consulting Micro, Small, and Medium Enterprises (MSMEs) in Pekanbaru City. Using a qualitative literature review approach, this article synthesizes findings from recent empirical and theoretical studies to provide a comprehensive understanding of how these three factors interact to influence employee motivation. The review highlights that competence, encompassing knowledge, skills, and abilities, is a fundamental driver of motivation, enabling employees to perform their tasks effectively and with confidence. Organizational culture, characterized by shared values, norms, and practices, creates an environment that can either foster or hinder motivation depending on its alignment with employee expectations and organizational goals. Tauhid, representing the integration of Islamic monotheistic values, is identified as a unique motivational factor within the context of Indonesian MSMEs, promoting a sense of purpose, ethical conduct, and spiritual fulfillment at work. The synthesis reveals that the interplay between competence, organizational culture, and tauhid not only enhances intrinsic motivation but also contributes to sustained organizational performance and employee well-being. The study concludes that a holistic approach, which integrates professional competence, supportive organizational culture, and spiritual values, is essential for fostering high work motivation in consulting MSMEs. Recommendations for future research include empirical investigations into the practical implementation of tauhid in organizational settings and its measurable impact on motivation and performance.